Elevated CO2 levels impact fitness traits of vine mealybug planococcus ficus signoret, but not its parasitoid leptomastix dactylopii howard - Schulze-Sylvester, Maria (2019)
Carbon dioxide (CO2) is one of the primary factors driving climate change impacts on plants, pests, and natural enemies. The present study reports the effects of different atmospheric CO2 concentrations on the vine mealybug Planococcus ficus (Signoret) and its parasitoid wasp Leptomastix dactylopii (Howard). We investigated the life-history parameters of both species on grapevine Vitis vinifera (L.) plants grown under elevated (eCO2) and ambient (aCO2) CO2 levels in a greenhouse and in a vineyard free-air carbon dioxide enrichment (FACE) facility. The greenhouse experiments with an eCO2 level of around 800 ppm showed a significant increase in survival rates, a strong trend towards declining body size, and an increasing fecundity of female mealybugs, while fertility and development time did not change. However, none of these parameters were altered by different CO2 concentrations in the VineyardFACE facility (eCO2 level around 450 ppm). On the other hand, the parasitism success, development time and sex ratio of L. dactylopii, reared on P. ficus under eCO2 or aCO2, varied neither in the greenhouse nor in the FACE facility. These results suggest that future CO2 levels might cause small-scale changes in vine mealybug fitness; however, this is not necessarily reflected by parasitoid performance.